Principles of Gene Manipulation - Old, R. W;Ed. Primrose, S. B;Ed (Studies in Microbiology, v. 2., 1989)
The authors provide an introduction to the subject, identifying and explaining basic principles. Completely updated, this edition provides an overview for researchers and students who already have some knowledge of recombinant DNA work.